The lexical-semantic study of Peruvian seafood - Uzuriaga, Jessica (2023)
This paper is a descriptive-explanatory investigation of Peruvian seafood lexicons. This article has two objectives: the first is to select and record the semantic features that make up the immanent and manifested meaning of Peruvian seafood lexicons; the second is to rank the lexicons according to semantic inclusion relations based on lexical fields. To do this, we use a descriptive structuralist methodology where we select and register a corpus of 30 names of Peruvian seafood extracted from Peruvian recipe books and gastronomic dictionaries and then group and describe them in minimal pairs that allow us to select the similar and differentiating semantic features; we also hierarchise the lexical fields found to account for the semantic relations of inclusion. In this way, we are able to determine the semantic features that allow us to transfer lexemes from a common language to a specialised language and to know the process of transitivity that exists in the semantic relations of inclusion in the lexicon of Peruvian seafood.